Kerja Perspektif Al-Qur'an (IAIN Ponorogo, 2011)
The moslem ethics of life is based on movement as expressed in certain terms like al-sharī’ah, al-tarīqah, al-sirāt, al-sabīl and al-manhaj, that make sense of way and teachings to achieve good life. Islam obliges and gives appreciation of the achievements of Muslims. The Qur’an uses several terms to refer to such work; ‘charity, kasb, juhd, ibtighâ’, sa ’yu and su ’âl. From this concept, the Qur’an considers work as noble, while begging is despicable. Work means thankful to God for the potential He bestows. The Qur’an promotes work not only because it is the way to achieve the wealth, but also because it possesses the its sacred value for the benefit of fulfilling livelihood. Therefore the work should also be done based on ethical values .